The Controversy on the Minimum Age for Marriage in Indonesia: Factors and Implications - Rismana, Daud; Hariyanto, Hariyanto; Azizah, Mabarroh; Zakiyah, Ninik; Hakimi, Abdul Rahim (Lembaga Contrarius Indonesia, 2024)
In 2019, Indonesia redefined the minimum age limit for marriage with the aim of achieving gender equality and reducing child marriage rates. Unfortunately, this legal reform did not entirely succeed and, instead, created a paradox within Indonesian society. This study aims to investigate the controversy surrounding the minimum age for marriage as stipulated in Indonesian Marriage Laws. The paper employs a socio-legal approach, collecting data through legal material investigation and interviews. The research indicates that the reformation attempt brings about at least three undesired implications: an increase in the number of marriage dispensations, child marriages, and pre-marital pregnancies. These paradoxes appear to be influenced by several factors: (1) the public's minimal awareness of the current marriage law, (2) the lack of socialization from government bodies, and (3) regulatory inconsistency itself. Theoretically, instead of resolving issues within society, it turns out that the legal changes initiated by the state do not significantly trigger changes within society.